Menopause status and attitudes in a Turkish midlife female population: an epidemiological study - Arslan Gul; Orsal Ozlem; Orsal Ozgul; Ayranci Unal; Emeksiz Dursun (BMC Women's Health, 2010)
Abstract Background It is a well accepted status that socio-cultural characteristics may affect the onset of menopause and its characteristics. The aims of this study were to describe the prevalence rates of menopausal symptoms and these symptoms related factors, and to assess the women's attitudes towards some climacteric issues. Methods This survey was conducted between Jan., 1st 2008 and March, 31st 2008 to research the menopause status of the female population in a city of western Turkey. The study group consisted of 1551 women selected with a multistage area sampling method: a random sample of individuals aged 40-65 years. The questionnaire included questions pertaining to women's sociodemographic characteristics, women's menopausal status, some statements about the climacteric, use of hormones at menopause or before menopause, and some climacteric myths. The data was analyzed by Chi-square (x2) analysis and percent (%) ratios with a significant value of P < 0.05. Results The mean age of the women was 49.1 years. Over 90% of the women were of the negative opinion that the climacteric is "the end of youth", "the end of fecundity", and "the end of unclean days". Most women said that cessation of menstrual periods was the most positive thing because they do not have to wait for monthly bleedings, use sanitary equipment, or take birth control methods. There were significant connections between age groups and nearly all the items, with the exception of the items "the end of life" and "the end of fecundity". Among the women, hot flushes were the most common complaint occurring in 96.5% of women: being severe in 32.9%, moderate in 43.1% and mild in 20.4%. This was followed by low backache or muscle pain 95.0% (25.9% severe, 46.0% moderate and mild 23.1%), headache 91.7% (21.9% severe, 34.9% moderate and 34.9% mild) and feeling tired 91.0% (15.3% severe, 38.6% moderate and 37.1% mild). Conclusions Most of the women in this study had mixed ideas of opinions concerning the climacteric, and the majority was also suffering from climacteric complaints. This data could assist healthcare providers in the provision of culturally competent health care to midlife Turkish women.